PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DAN MODEL PEMBELAJARAN INDIVIDUAL DENGAN MENGGUNAKAN MINI LAB UNTUK MENINGKATKAN HASIL BELAJAR SMA SWASTA MEDAN - Siregar, Hotma Tiolina (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This researc was aimed to investigate the differences between aplication of cooperative learning model and individual model using Mini Lab in biology class withs the topic reproduction system in private schools in Medan. The metodology that using in this research is experimental method with application of cooperative learning model at class XI-A SMA YPI and at class XI-A SMA AL-washliyah, then at class XI-B SMA YPI and at class XI-B SMA AL-washliyah using individual model. From the data analysa showed the mean of biology test with appliction of cooperative learning model is 7,61 and standart deviation is 0,34, Meanwhile the mean of biology test with aplication of individual learning model is 6,09 and standart deviation is 0,34. Then hypotheses test with t test show hitung > t table, then ho is rejected and alternatife is excepted.Â Keywords: Cooperative Learning, Model, Individual